A Manifest against Optimism and Self-consciousness: A Critique of the Philosophy of Arthur Schopenhauer Based on the Book of "Ethics, Law, and Politics” - Reza Nasiri Hamed (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book of Ethics, Law, and Politics includes the translation of the essays by famous German philosopher Arthur Schopenhauer. The various sections of the book encompass concrete issues that Schopenhauer has, like any other philosopher, expounded on the basis of his ontological and epistemological foundations. In this paper, we try to survey his ontological, epistemological, and methodological foundations, as well as the relation between the conditions and the context of his personal and social life with his thoughts, to understand his most important concerns. Also, while referring to the structure of this book in terms of its form and content, the relation of our current world to the Schopenhauer's thoughts and reflections is analyzed briefly. An important issue in Schopenhauer's political and social ideas is the role of blind and aimless will as the ontological basis of his views, which has led to a bitter insight toward man and political life. However, he places great emphasis on human life, especially on ethics as a relationship between human beings and the art. So, despite his pessimistic and tragic point of view, he is trying to provide a clear vision of life.